Reklamasi pantai berkaitan dengan status hukum tanah dan pendapatan daerah dalam tatanan negara Indonesia - H Muhamad Rezky Pahlawan MP (PROGRESIF: Jurnal Hukum, 2020)
The need for land has become a very important demand explosion due to the vast area of ​​the city of Jakarata which is already very dense. So that reclamation becomes one of the efforts in increasing the region as well as regional income. The purpose of this research is to provide a clear and formal explanation for both the regional government and the general public. The writing uses an empiric juridical method with a positive written legal approach that is applied to in concreto legal events in society. . This can affect the legal subjects holding rights from land reclaimed by the beach. The legal status of the legal subject to management rights is still regulated by general regulations so that it can lead to multiple interpretations of legal subjects that hold management rights from land reclaimed by the beach. Regional Governments should be able to prepare legal infrastructure in accordance with the existing laws and regulations and can also have a positive effect on the business world as well as the economic sector.